The Importance of Service Entities for the Furniture Industry in Poland - The Perspective of Network Relationships and Cooperation - Ratajczak-Mrozek, Milena; Herbeć , Magdalena (Studia Oeconomica Posnaniensia, 2014)
Within the network approach, companies are seen as part of a wider system of relationships between many actors (entities), activities and resources. In this article the perspective of network relationships and cooperation is adopted to analyse furniture companies in Poland and their relationships with service entities. The purpose of the article is to assess the importance of close cooperation between companies from the furniture industry and service entities. The basis for this assessment is the ARA model (Actors - Resources - Activities), which creates a framework for the analysis of network relationships. The ARA model identifies the key actors and characterises the actions that connect them and the resources which are exchanged by them. The article demonstrates that the mutual commitment of resources of furniture manufacturers and service operators is a manifestation of the multidimensionality of the interrelations between the entities in this market. Due to the dominant share of micro and small enterprises in the structure of the furniture industry, many furniture manufacturers typically prefer to produce the final product on their own. As a result, the relationships between furniture companies and service providers are diversified and depend on the size of the companies as well as the scope of their business activities. Thus, while strong relationships often occur between large furniture producers and service companies from the furniture sector (for example firms providing services in the field of joinery and upholstery), in the case of smaller manufacturers a relatively low frequency and short duration of interactions predominate. The links between furniture producers and service companies outside the furniture industry are diverse as well. The analysis presented of the importance of service entities for the furniture industry shows that the potential of close cooperation is not being fully utilised.